Music Mnemonics in Boosting Students' Vocabulary - Astri Nursamsi Harahap; Sri Rahmadhani Siregar; Khusnul Khatimah (Journal of English Language Teaching, Linguistics, and Literature Studies, 2026)
This study examined the effectiveness of the Music Mnemonic Technique in enhancing students’ vocabulary mastery. Employing a quantitative pre-experimental approach with a one-group pretest–posttest design, the research involved 30 eighth-grade students of SMP N 8 Padangsidimpuan. Vocabulary achievement was assessed through a validated multiple-choice test administered prior to and following the intervention. The findings revealed a statistically significant improvement in students’ vocabulary performance, as indicated by the increase in the mean score from 57.87 (pre-test) to 81.00 (post-test). Statistical analysis using a paired-samples t-test confirmed a significant difference between pre-test and post-test results, t (29) = 3.303, p < .05. The effect indicates that integrating musical elements into mnemonic-based instruction facilitates vocabulary retention and recall. The study concludes that the Music Mnemonic Technique constitutes an effective pedagogical strategy for vocabulary instruction at the junior secondary level. These findings contribute to the growing body of research supporting multimodal and cognitively oriented approaches in foreign language learning.Keywords: EFL Instruction, Music Mnemonic Technique, Pre-Experimental Research, Vocabulary Acquisition